How to do biography : a primer - Hamilton, Nigel (Harvard University Press, 2008)
Following his recent Biography: A Brief History (from Harvard), award-winning biographer and teacher Nigel Hamilton tackles the practicalities of doing biography in the first succinct primer to elucidate the tools of the biographer's craft.
Keywords: Biography as a literary form.; Biography -- Research -- Methodology.; Autobiography -- Authorship.; Biography.; Biographie (Genre littéraire); Biographies -- Recherche -- Méthodologie.; Biographies.; biographies (literary genre); biography (general genre); LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; Autobiography -- Authorship; Biography as a literary form; Biography -- Research -- Methodology